ECONOMIC HISTORY OF IGALA WOMEN IN KOGI STATE, 1900 – 2020 - SOPHIA OJOCHOGWU ADOFU (International Studies Journal)
This paper explores the economic history of Igala women in Kogi State, Nigeria. It delves into the historical context of Igala society, examining the traditional roles and economic activities of women within the community. Through a comprehensive analysis of historical records, oral traditions, and scholarly research, this paper elucidates the significant contributions of Igala women to the economic development and sustenance of their families and communities. Furthermore, it discusses the challenges and transformations experienced by Igala women in the face of modernization and socio-economic changes. By shedding light on the economic endeavors of Igala women, this paper contributes to a deeper understanding of gender dynamics and economic development in Nigerian society.